Melatonin attenuates neurogenic pulmonary edema via the regulation of inflammation and apoptosis after subarachnoid hemorrhage in rats. Issue 4 (23rd October 2015) - Chen, Jingyin; Qian, Cong; Duan, Hongyu; Cao, Shenglong; Yu, Xiaobo; Li, Jianru; Gu, Chi; Yan, Feng; Wang, Lin; Chen, Gao
Abstract: Neurogenic pulmonary edema (NPE) is a serious non‐neurological complication that can occur after a subarachnoid hemorrhage (SAH) and is associated with decreased survival and a poor neurological outcome. Melatonin is a strong antioxidant that has beneficial effects against SAH in rats, including reduced mortality and reduced neurological deficits. The molecular mechanisms underlying these clinical effects in the SAH model, however, have not been clearly identified. This study was undertaken to determine the influence of melatonin on SAH‐induced NPE and the potential mechanism of these effects using the filament perforation model of SAH in male Sprague Dawley rats. Either melatonin (150 mg/kg) or a vehicle was given via an intraperitoneal injection 2 hr after an SAH induction. Lung samples were extracted 24 hr after SAH. The results show that the melatonin treatment attenuated SAH‐induced NPE by preventing alveolar–capillary barrier dysfunctions via inhibiting the disruption of tight junction proteins (ZO‐1 and occludin). Moreover, the treatment downregulated the levels of mature interleukin (IL) ‐1 β, myeloperoxidase (MPO), and matrix metallopeptidase (MMP) 9 expression/activation, which were increased in the lung; also, melatonin treatment improved neurological deficits. Furthermore, the melatonin treatment markedly reduced caspase‐3 activity and the number of TUNEL‐positive cells in the lung. Taken together, these findings show that administration of melatonin attenuates NPE by preventing alveolar–capillary barrier dysfunctions via repressing the inflammatory response and by anti‐apoptosis effects after SAH.